Multiple Infrastructure D&B Project Management in Rural Areas in Malaysia - C.T, Ramanathan; Sambu Potty, Narayanan; M. Taharin, Radzif (2007)
Selected infrastructure projects are being implemented by Design and Build procurement system in Sabah (East Malaysia). In these development projects, 45 Bridges in bridge replacement projects together with two Road projects are being executed simultaneously by the author’s Design and Build firm. The former were awarded in 5 packages in the first phase of Bridge replacement project for PWD. The latter are constructed for Ministry of Rural development. The company manages such projects by using established systems for design, contract, contract administration, construction execution and supervision. Engineers from qualified engineering bodies are selected and appointed for In-house design team / supervision team. Team - discussion and inputs in selecting critical bridge components including (i) Methods of pile foundation, (2) Selection of suitable beam technologies, (3) No. of spans, etc are explained. Majority of the construction works are executed directly by main contractor with appointed specialist contractors for piling works and beam production. Subcontractors for execution of selective works were decided by the Management by contracting and bidding. Aspects of specialist works, diversion works, temporary works, construction program, and management, project cost estimation, tendering and final close out are discussed. This paper gives solutions for the complications in the management and recommendations for improvement in management of multiple design and build project.